ANALISIS PRODUKSI DAN KEBUTUHAN PADI UNTUK KONSUMSI MASYARAKAT DI KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - hamdani hamdani; Ernawati Ernawati; Triyatno Triyatno (JURUSAN GEOGRAFI FIS UNP, 2020)
Land over function is a change in the function of some or all land areas of the original function (as planned) into another function. These changes have a negative impact (problems) on the environment and potential of the land itself. One of these changes took place in West Pasaman Regency, especially on wet farms (rice fields) into oil palm plantations. It makes the production of rice fields decrease, and has an impact on the availability of rice for society. This research aims to see how much rice production is and how the availability of food (rice) for the community in the district of Luhak Nan Duo, West Pasaman Regency. Therefore, the availability of food, especially rice in the district of Luhak Nan Duo can be fulfilled and assured for the long term. This research uses a quantitative descriptive method which provide a real potrait of the variables obtained to get the real situation. The variables in this study are, land area, amount of rice production, number of inhabitants, and the rice needed percapita. The data collection techniques are, study document to find the population of the residents, interviewing the farmer to know how rice paddy management, and observation to find out the area of existing rice fields. The method of the data analize is using descriptive quantitative. The result of the research shows that the production of the rice in Luhak Nan Duo increased. But it has not fulfilled the needs of the residents in Luhak Nan Duo. It means that Luhak Nan Duo has not self-sufficient in rice yet.